Caspase 9 Promoter Polymorphisms (-1263G>A, -905T>G, -712C>T) in Coronary Artery Disease - KISHORE KUMAR GUNDAPANENI; NIVAS SHYAMALA; KAUSHIK PURANAM; RAJESH KUMAR GALIMUDI; KEERTHI KUPSAL; KRISHNA REDDY NALLAMALA; SUREKHA RANI HANUMANTH (Journal of Clinical and Diagnostic Research, 2020)
Introduction: Apoptosis has been involved in a number of pathological conditions including Coronary Artery Disease (CAD). Caspases are important regulators and executioners in both extrinsic and intrinsic apoptotic pathways. Caspase 9 is an initiator caspase involved in intrinsic apoptotic pathway activated by mitochondrial damage and cytochrome c, forms an apoptosome with procaspase-9 and activates the CASP9 cascade to execute apoptosis. Aim: To evaluate the association between CASP9 (-1263G>A, -905T>G, -712C>T) genotypes/haplotypes and their susceptibility to CAD. Materials and Methods: This case-control study consisted of 300 CAD patients admitted in Durgabai Deshmukh Hospital and Research centre, Hyderabad, Telangana, India, along with 300 age and gender matched healthy controls from local population between January 2012 to December 2016. The DNA samples were genotyped for polymorphisms in CASP9 (-1263G>A, -905T>G, -712C>T) by Polymerase Chain Reaction-Restriction Fragment Length Polymorphism (PCR-RFLP) method. The data of CAD cases and controls were compared using the Student’s t-test for continuous variables and a Chi-square test for categorical variables using online statistical tools such as Interactive Chi square analysis and OpenEpi version 3.03. Linkage Disequilibrium (LD) and haplotype analysis were carried out by Haploview software. Interaction between single nucleotide polymorphisms and epidemiological parameters were determined by Multifactor Dimensionality Reduction (MDR) analysis. Results: Molecular analysis revealed that TG, TT genotypes of CASP9 -905T>G, -712C>T conferred 3 and 17 fold risk respectively for the development of CAD. Promoter polymorphic combinations of CASP9 were in perfect LD in controls. G-T-C, A-T-C haplotype of -1263G>A, -905T>G, -712C>T polymorphisms were found to be significantly predominant in the disease group. Further, MDR analysis showed that caspase 9 -712C>T polymorphism with positive family history, consumption of beverages and alcohol have high degree of redundancy. Conclusion: The present study suggests that CASP9 -712C>T variant might be used as a diagnostic marker for susceptibility to CAD.